Bilateral Inguinal Ulcerations as First Presentation of Acute Myeloid Leukaemia - Jana Dorothea Braun; Cyrill Géraud; Alexander Marx; Andreas Reiter; Mohamad Jawhar; Jan P. Nicolay (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)